(untitled) (Colombia Medica, 2024)
Aim: To identify the main components related to the thoughts and erotic practices of students at Universidad del Valle, San Fernando Campus. Method: A descriptive study was conducted during 2008-2009 to evaluate the students´ necessities on sexual and reproductive health (SRH) in two faculties in a public university in Valle del Cauca, Colombia. A total of 1120 students were evaluated. Results: An information technology system was designed for this study. Six hundred and ninety five (62%) of the subjects were women with an average age of 20 years, mostly coming from underprivileged economic backgrounds. The average age for the beginning of sexual intercourse was 16 without differences by educational level. Fifty percent had their first intercourse before their final adolescence, 42.3% have had 2 to 5 sexual partners. Women enjoy sex with less frequency than men (p=0.022). Men have higher frequency of sexual intercourse outside of the couple than women (p=0.001). Conclusions: Men adopted risk behaviors in erotic practices such as more sexual couples, high frequency of unfaithfulness. Men report more pleasure in their erotic practices.